2013
DOI: 10.9790/1959-0145670
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Experiences toward Perception of Medication Administration Errors Reporting

Abstract: Wakefield et al. (1996) and was modified by the researchers. It contained 65 questions; 29 items regarding reasons why medication errors occur, 16 items regarding reasons why medication errors not reporting and 20 items regarding what percentage of each type of medication error actually reported on units which divided into 9 items for non intravenous and 11 items for intravenous medication administration errors. Results: This study suggested five categories for reasons of why MAEs occur and three categories f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 26 publications
2
21
3
Order By: Relevance
“…36 The current study also found that the response by nursing administration does not match the severity of the error 61 (40.9%) comparable to the recent findings from a study in Kirkuk city hospitals whereby 57.3% of nurses fear the administration reasons. 37 On the other hand, the lowest answer was disagreement of error definition with 8 (5.4%) contrarily to the findings from the study that found that disagreement over time and error definition is the third leading cause of not reporting the MAEs by the echelon of 36.6%. 36 Concerning the socio-demographic data and barriers to self-reporting after committing an error, the results revealed that there was statistical significance all variables in socio-demographic.In dissimilarity to the results of the study that was conducted in Turkey which revealed no statistical significance regarding experience and reporting.…”
Section: Barriers To Self-reportingcontrasting
confidence: 41%
See 1 more Smart Citation
“…36 The current study also found that the response by nursing administration does not match the severity of the error 61 (40.9%) comparable to the recent findings from a study in Kirkuk city hospitals whereby 57.3% of nurses fear the administration reasons. 37 On the other hand, the lowest answer was disagreement of error definition with 8 (5.4%) contrarily to the findings from the study that found that disagreement over time and error definition is the third leading cause of not reporting the MAEs by the echelon of 36.6%. 36 Concerning the socio-demographic data and barriers to self-reporting after committing an error, the results revealed that there was statistical significance all variables in socio-demographic.In dissimilarity to the results of the study that was conducted in Turkey which revealed no statistical significance regarding experience and reporting.…”
Section: Barriers To Self-reportingcontrasting
confidence: 41%
“…35,36 However, the omission of a drug with the lowest percentage is similar to the study done at Benioff children's hospital. 37 Even if the wrong time comes on the top for the present study may be due to nurse patient ratio but dosing error is very crucial in pediatric clients as the simple error in dosing may lead to the greater risk to their health and requires weight related calculations compared to adults prescriptions. 38 The present results have suggested the significant association between the types on MAEs with the sociodemographic data except the sex of the participants (p=.039).…”
Section: Types Of Maesmentioning
confidence: 99%
“…This includes prescribing; sequence communication; drug-labeling, packaging, absence of knowledge about medication administration, misinterpretation of oral directions and compounding; dispensing; distribution; administration; education; follow-up; and use (Johnson et al, 2011). A medication could basically happen in the form of time and rate mistaken timing, either mistaken dose or drug to patients (Weant et al, 2014), and hence, it can reduce medication errors and increase patients' safety that represents a basic concern of hospitals quality enhancement and problem solving (Al-Youssif et al, 2013). This should be based on the design and puts into effect more error-resistant systems and creates an environment in which staff can learn from failure -a safe, non-penal environment that may support staff handling of mistakes, their reasons, together with strategies of eliminating such mistakes (Hughes and Blegen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…4 It is more than a simple psychomotor task. It reflects a complex interaction of a large number of specific decisions and actions 5 and involves skillful technique and consideration of the patients' development, health status and safety. The nurse administering medication needs knowledge about drugs including drugs name, preparation, classifications and adverse effects and physiological factors that affect drug actions.…”
Section: Introductionmentioning
confidence: 99%
“…10 Thus, safe administration of medication is very important to nurse, doctor, administrator, patient and public and the entire health care system. 5 Administering medicines to the patients according to the defined procedure and policy reduce the risk of error, and assure the patients safety. Therefore this study aims at finding out the nurses' practice of administering medicine to the patients by oral route.…”
Section: Introductionmentioning
confidence: 99%